2016
DOI: 10.1111/ced.12977
|View full text |Cite
|
Sign up to set email alerts
|

What's new in atopic eczema? An analysis of systematic reviews published in 2014. Part 1. Epidemiology, risk factors and outcomes

Abstract: SummaryThis review summarizes key findings from nine systematic reviews on atopic eczema (AE) published or first indexed in 2014. It focuses on epidemiology, disease processes and methodological issues. There is reasonable evidence to conclude that high birth weight (> 4000 g) is a risk factor for the development of AE. A lower socioeconomic position is associated with lower prevalence of AE. The effect of exposure to traffic-related air pollution in childhood on the development of AE is uncertain. CD14 polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Its high prevalence puts a considerable burden on both eczema sufferers and society and negatively impacts the quality of life for a large number of individuals. 5,6 A growing body of literature supported that the environmental factors such as temperature, relative humidity, wind speed and air pollutants may play important roles in the exacerbation of eczematous rashes. 3,4 Eczema is usually caused by allergic contact dermatitis, atopic dermatitis and irritant contact dermatitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its high prevalence puts a considerable burden on both eczema sufferers and society and negatively impacts the quality of life for a large number of individuals. 5,6 A growing body of literature supported that the environmental factors such as temperature, relative humidity, wind speed and air pollutants may play important roles in the exacerbation of eczematous rashes. 3,4 Eczema is usually caused by allergic contact dermatitis, atopic dermatitis and irritant contact dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that lots of internal and external factors provoked eczematous lesions, including genetic predisposition, stress, infections, food intake, inhalant allergens and other daily objects. 5,6 A growing body of literature supported that the environmental factors such as temperature, relative humidity, wind speed and air pollutants may play important roles in the exacerbation of eczematous rashes. 7 Several studies suggested that seasonal climate changes might lead to the seasonal variation of prevalence and clinical features in eczema.…”
Section: Introductionmentioning
confidence: 99%
“…For an update of SRs on the methodological issues and epidemiology of AE, see Part 1 of this update. Similar evidence updates on AE have been published previously, along with the details of the search methods used …”
Section: Introductionmentioning
confidence: 91%
“…Odds ratio (95% CI) We used proximity to the closest major road and density of nearby roads, as proxies for exposure to TRAP, to assess the associations between TRAP exposure and allergic diseases of children. Although many previous epidemiological studies of allergic diseases used exposures to traffic-related air pollutants such as PM 2.5 and NO , other studies also reported relationships using traffic indicators [25,[40][41][42][43][44]. These metrics help us focus on air pollution directly related to traffic, whereas it is difficult to isolate the impact of traffic when we use individual pollutants affected by various sources other than traffic [25,45].…”
Section: 6mentioning
confidence: 99%